TANTANGAN PEMERINTAH INDONESIA DALAM MENGHADAPI GIG ECONOMY - Ratih Latif Pramana; Sugiyanto (CV. Adiba Aisha Amira, 2024)
The gig economy or digital economy has had a positive impact on the economy in Indonesia with an estimated valuation of reaching 100 billion USD in 2025 (E. & Nasution, H.S. 2020). Go-Jek is a form of gig economy that has extraordinary appeal at the moment. The aim of this research is to find out the extent of the development of the platform-based gig economy in Indonesia and how the government handles various kinds of challenges that will occur due to the rapid growth of the gig economy in Indonesia. Indonesia today and in the future. Research data was obtained through secondary data by using a descriptive research method approach such as literature study and legislation study. It is hoped that from this research the government will be able to answer the current challenges, the rapid growth of the digital-based economy is something to be grateful for, but on the other hand, the gig economy is not a stable or permanent job, there is no guarantee of the future like ASN. Therefore, it is necessary to implement policies that can facilitate gig economy workers as a manifestation that the government is on the side of gig economy actors, who currently number approximately 46.47 million people, approximately 32% of the total workforce of 146.62 million people (Data BPS 2023).